Pengembangan Media Radely Interactive Slide Genially untuk Meningkatkan Keterampilan Menulis Teks Prosedur - Fitri, Salwa Azzahra; Khaerunnisa, Khaerunnisa (Program Studi Pendidikan Bahasa dan Sastra Fakultas Keguruan dan Ilmu Pendidikan Universitas Jambi, 2025)
The use of digital learning media plays an important role in improving the quality of Indonesian language learning, particularly students’ procedural text writing skills at the junior high school level. The low writing ability of students indicates the need for more interactive and learner-oriented instructional media. This study aimed to develop and evaluate the feasibility of Radely media based on Interactive Slide Genially for teaching procedural texts. The research employed the ADDIE development model, consisting of analysis, design, development, implementation, and evaluation stages. The research subjects were seventh-grade students of SMP Negeri 28 Tangerang. The validation results showed that the Radely media was categorized as very feasible by media experts (93%), material experts (100%), and language experts (98%). Teacher assessment of media practicality reached 88% and was classified as very good. Furthermore, student responses in the preliminary and main field trials achieved percentages of 90% and 94%, respectively, both in the very good category. These findings indicate that Radely media is effective in supporting systematic, engaging, and linguistically appropriate procedural text writing instruction, and is therefore suitable as an innovative digital learning medium at the junior high school level.